Video-assisted thoracoscopic double lobectomy for bronchiectasis: A case report and literature review - Toshiaki Takahashi; Tadaharu Okazaki; Takashi Doi; Hiroyuki Koga; Kenji Suzuki; Geoffrey J Lane; Atsuyuki Yamataka (Wolters Kluwer Medknow Publications, 2013)
Although thoracoscopic lobectomy for severe bronchiectasis has been reported in children, this is the first report of double lobectomy of the right middle and lower lobes performed using the video-assisted thoracoscopy in a 9-year-old girl. The post-operative course was uneventful and she is currently well after 18 months' follow-up.